2007
DOI: 10.1136/jmg.2007.050930
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with HD CAG repeat instability in Huntington disease

Abstract: Significant sibling-sibling correlation for repeat instability suggests that genetic factors play a role in intergenerational CAG repeat instability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
100
5

Year Published

2008
2008
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 116 publications
(113 citation statements)
references
References 30 publications
8
100
5
Order By: Relevance
“…In our study, the maternal transmission of longer expanded alleles was more frequently observed in sons than in daughters. These results are similar to that reported by Wheeler et al 31 We found that a greater variation in number of CAG occurred when the HD allele was paternally transmitted, and the only repeat contraction occurred when the mutation was maternally transmitted to a son. Wheeler et al 31 observed a greater number of repeat contractions when the allele was transmitted from mothers to daughters.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…In our study, the maternal transmission of longer expanded alleles was more frequently observed in sons than in daughters. These results are similar to that reported by Wheeler et al 31 We found that a greater variation in number of CAG occurred when the HD allele was paternally transmitted, and the only repeat contraction occurred when the mutation was maternally transmitted to a son. Wheeler et al 31 observed a greater number of repeat contractions when the allele was transmitted from mothers to daughters.…”
Section: Discussionsupporting
confidence: 92%
“…In our survey, the mean size of the paternally inherited CAG alleles was 42.25±2.6 repeats. A similar result was found in the Venezuelan kindred study, 31 which showed a mean value of 44.4 CAG repeats.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations